(3LfI GdQVi aj GdJSdje deG bOQ Gddg hbVis - (3eMeO Hf eMeO Hf eMeO GHf YGUe GdbjSj GdCfOdSj GdZQfGWj, CHhjMji,J (B857 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi jbQQg GdMRf hGdaQM CeG HYO aEf ai MhGOK GdCjGe GdChdi GdCagGe s
(3BNQgG (B:s
(3hgj Cf jchf GdEHJdGA ai GdfahS heG eYgG hGbYG ai GdMGd hBNQ eG ajg hGdMeO ddg HGdeMGeO GdJi jKfi HgG Ydi faSg hUdi Gddg Ydi eMeO hYdi Bdg hSde JSdjeG cKjQG s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B48 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B293 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B199s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs